Empowering young minds: An e-book intervention to boost earthquake disaster literacy - Ananda Pratiwi; Heny Aryani; Nia Wati; Luthfiyaul Laila; Antomi Saregar; Husni Mubarok; Utama Alan Deta (Journal of Advanced Sciences and Mathematics Education, 2023)
Background: Education on disaster mitigation remains critically underemphasized, with existing pedagogical approaches often falling short in adequately preparing children for the realities of natural disasters. This gap underscores the urgent need for innovative educational tools that can effectively enhance disaster literacy among younger populations.Aim: This study aims to develop and assess an Earthquake E-Book designed to elevate the disaster literacy levels among children, focusing on its validity, practicality, and effectiveness as educational media.Method: Employing a Research and Development (RnD) framework, the study navigated through stages of problem identification, design formulation, and implementation, excluding the evaluation phase to concentrate on the developmental process. The implementation employed a One-Group Pretest-Posttest design, involving pretesting, intervention (treatment), and posttesting phases. The e-book's validity was appraised by three expert validators, while its practicality was gauged through student questionnaires, and its effectiveness was measured using the N-Gain test on student learning outcomes.Results: The Earthquake E-Book garnered an average validation score of 85.4 percent, positioning it within the valid category. Practicality assessments reflected an 85.4 percent efficiency rating from student feedback. Furthermore, the effectiveness, as indicated by an N-Gain score of 0.74, was classified within the high category, signifying substantial improvements in children's disaster literacy post-intervention.Conclusions: The findings affirm that the Earthquake E-Book stands as a valid, practical, and effective educational tool in bolstering disaster literacy among children. By integrating this digital resource into disaster mitigation education, it is anticipated to significantly contribute to enhancing children's understanding and preparedness for earthquake disasters.